The use of a vascularized fibular flap in the treatment and surgical rehabilitation of military trauma patients - Badiul, P. O.; Sliesarenko, S. V.; Rudenko, O. I. (Zaporozhye Medical Journal, 2024)
Aim. The purpose of the work is to demonstrate the possibilities of using a vascularized fibular flap to replace bone defects in the treatment of acute military trauma and its consequences at the rehabilitation stage. Materials and methods. An anatomical feature description of the vascularized fibular flap with a cutaneous component. Clinical cases of the vascularized fibular flap use to reconstruct bone and soft tissue defects after military injuries. In the presented cases, vascularized fibula osteocutaneous flaps were used. Results. Two clinical cases of reconstruction using the fibula flap are presented. The first case presents a patient with a total mandibular defect resulting from a gunshot wound. The second case presents a patient with consequences of a mine-shrapnel injury of the left forearm and an ulnar defect of about 12 cm in length and the resultant inability to perform rotational movements. Vascularized fibula osteocutaneous flaps were used for reconstruction in both cases being transferred to the recipient site, and microvascular anastomoses were performed for flap reperfusion. Conclusions. Adding a free fibula flap to the reconstructive surgeon’s arsenal enables one-stage reconstructions of large wounds with bone defects after injuries or oncological resections without significant musculoskeletal functional loss to donor limbs.